Peningkatan Kompetensi Guru dalam Pengelolaan Kelas melalui Teknologi Digital - Ahmad Zaki; Diani Syahfitri; Devita Sari Nst (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Training in digital technology for elementary school teachers is a solution to enhance classroom management skills and teaching quality. This study aims to evaluate the impact of digital technology training on teachers' skills and social changes within the educational community. The methods used include initial surveys, practice-based training, and post-training evaluations with qualitative and quantitative approaches. The results show a significant improvement in teachers' technology skills and positive changes in classroom management. Teachers reported increased confidence and practical skills in using technology tools, and the formation of support groups and technology-based learning communities. The program also facilitated the emergence of local leaders who spearhead technology initiatives in their schools. These findings emphasize the importance of participatory and sustainable training in creating positive changes within the educational environment.